PERANCANGAN SMART AQUARIUM BERBASIS INTERNET OF THINGS (IOT) - Ikhsyan, Muhammad Nur; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2022)
Ornamental fish has become a fishery commodities that have greats potentials to be developed. Keeping ornamentals fish is one of the populars hobbies in developed countries and is gaining popularity in many developing countries. The aquarium is one of the containers for cultivating and maintaining ornamental fish, both freshwater and seawater fish. Ornamental fish can live and grow well in an aquarium requiring some good care including feeding, oxygen, light, and good water quality. Timely feeding and monitoring of water conditions in the aquarium is not easy. Ornamental fish owners usually pay less attention to water conditions because they are busy. Therefore we need a water condition monitoring system and automatic feeding. This study aims to design an internet of things (iot)-based smart aquarium that can monitor pH, temperature and turbidity of aquarium water as well as an IoT-based automatic feeding system. Design a smart aquarium using NodeMCU ESP8266, pH Sensor SEN0161, Temperature Sensor DSB18B20, Turbidity Sensor SEN0189. The design in this research includes hardware design (electrical and mechanical) and software design. Monitoring and controlling of this system can be done using a smartphone that is connected to the controller via auth from the blynk application. Testing on the tool using an aquarium. The results of the study concluded that the design of a smart aquarium based on the internet of things (iot) can work well